Guidelines for office gynecology in Japan: Japan Society of Obstetrics and Gynecology (JSOG) and Japan Association of Obstetricians and Gynecologists (JAOG) 2017 edition. Issue 4 (24th January 2019) - Kawaguchi, Ryuji; Matsumoto, Koji; Akira, Shigeo; Ishitani, Ken; Iwasaku, Kazuhiro; Ueda, Yutaka; Okagaki, Ryugo; Okano, Hiroya; Oki, Toshimichi; Koga, Kaori; Kido, Michiko; Kurabayashi, Takumi; et al.
Abstract: Six years after the first edition of The Guideline for Gynecological Practice, which was jointly edited by The Japan Society of Obstetrics and Gynecology and The Japan Association of Obstetricians and Gynecologists, the third revised edition was published in 2017. The 2017 Guidelines includes 10 additional clinical questions (CQ), which brings the total to 95 CQ (12 on infectious disease, 28 on oncology and benign tumors, 27 on endocrinology and infertility and 28 on healthcare for women). Currently a consensus has been reached on the Guidelines and therefore the objective of this report is to present the general policies regarding diagnostic and treatment methods used in standard gynecological outpatient care that are considered appropriate. At the end of each answer, the corresponding recommendation level (A, B, C) is indicated.